Ab initio molecular dynamic simulation of Zn-Al-Fe alloys - Zhang H.; Zhao J.; Pu Z.; Li Y.; Xu B.Q.; Yang B. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2019)
This paper presents the measurement of the Ab initio molecular dynamics of a Zn-Al-Fe alloy system. The structural and electronic properties of the Zn-Al-Fe alloy at different temperatures are simulated, and the partial density of states, radial distribution function, coordination number, mean square displacement, and diffusion coefficient are obtained. It provides a theoretical analysis of the vacuum separation of Zn-Al-Fe alloys. The simulation results show that when the temperature was 1073 K, the disorder degree of the system was the largest, the diffusion coefficient was 1.29（10−8m2s−1), and the coordination number was 9.48. It means that the Zn-Al-Fe alloy can be separated into its constituent metals easily by vacuum distillation, and that the optimum temperature to achieve this is 1073 K.